2021
DOI: 10.2147/dmso.s312527
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Similarities and Differences in Metabolic Actions and Effects of Central Nervous System Between Glucagon-Like Peptide-1 Receptor Agonists (GLP-1RAs) and Sodium Glucose Co-Transporter-2 Inhibitors (SGLT-2is)

Abstract: GLP-1 receptor agonists (GLP-1RAs) and SGLT-2 inhibitors (SGLT-2is) are novel antidiabetic medications associated with considerable cardiovascular benefits therapying treatment of diabetic patients. GLP-1 exhibits atherosclerosis resistance, whereas SGLT-2i acts to ameliorate the neuroendocrine state in the patients with chronic heart failure. Despite their distinct modes of action, both factors share pathways by regulating the central nervous system (CNS). While numerous preclinical and clinical studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 193 publications
(184 reference statements)
0
6
0
Order By: Relevance
“…These metabolites are biologically active, can reduce intravascular oxidative stress, inhibit hepatocyte gluconeogenesis and oxidative stress, increase cardiomyocyte activity, promote vasodilation, protect the cardiovascular system, improve cardiac function, thereby directly or indirectly protecting the cardiovascular system ( 80 82 ). For example, a number of large-scale clinical trials have demonstrated that GLP-1RA could reduce the risk of cardiovascular events, which has been well reviewed in elsewhere ( 83 , 84 ) and we will not further discuss here.…”
Section: The Role Of Glp-1/glp-r In Related Diseasementioning
confidence: 99%
“…These metabolites are biologically active, can reduce intravascular oxidative stress, inhibit hepatocyte gluconeogenesis and oxidative stress, increase cardiomyocyte activity, promote vasodilation, protect the cardiovascular system, improve cardiac function, thereby directly or indirectly protecting the cardiovascular system ( 80 82 ). For example, a number of large-scale clinical trials have demonstrated that GLP-1RA could reduce the risk of cardiovascular events, which has been well reviewed in elsewhere ( 83 , 84 ) and we will not further discuss here.…”
Section: The Role Of Glp-1/glp-r In Related Diseasementioning
confidence: 99%
“…26,27 In addition, GLP-1 RAs have been shown to have a variety of benefits, including reducing the risk of cardiovascular events, improving microvascular function, and reducing inflammation. [28][29][30][31] While GLP-1 RAs are more costly compared with older glucoselowering agents, lower inpatient and outpatient health care costs among patients have been shown to offset the higher treatment costs, resulting in budget neutrality compared with other glucose-lowering agents. 32 Despite the benefits, the use of these medications has remained limited.…”
Section: Introductionmentioning
confidence: 99%
“…Glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs) are a recommended first‐line treatment option for T2DM because of their effectiveness in regulating blood glucose levels and the additional benefit of weight reduction 23‐25 with minimal well‐known adverse events 26,27 . In addition, GLP‐1 RAs have been shown to have a variety of benefits, including reducing the risk of cardiovascular events, improving microvascular function, and reducing inflammation 28‐31 . While GLP‐1 RAs are more costly compared with older glucose‐lowering agents, lower inpatient and outpatient health care costs among patients have been shown to offset the higher treatment costs, resulting in budget neutrality compared with other glucose‐lowering agents 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GLP-1RAs have been shown to exert many beneficial effects on vascular endothelial cells. For instance, GLP-1RAs were demonstrated to reduce the risk of cardiovascular events (5) by decreasing the blood pressure (6), improving microvascular function, and reducing inflammation (7). Further, GLP-1RAs play a neuroprotective effect by stimulating the differentiation of nerve cells and inhibiting neuroinflammation (8), while they were also reported to inhibit liver inflammation (9).…”
Section: Introductionmentioning
confidence: 99%